Improving Indonesian Language Learning Outcomes by Using the Canva-Based PjBL Learning Model for Class 5 Students' Writing Elements (phase c) UPTD SDN 35 Barru - Agus, M.; Saskia, Saskia; Sari, Sri Windy; Abbas, M. Riswan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to improve the learning outcomes of Indonesian language in the writing element of grade V students (Phase C) by implementing the Canva-based Project-Based Learning (PjBL) learning model at UPTD SDN 35 Barru. This research method uses classroom action research (PTK) which is carried out in two cycles. Each cycle consists of planning, implementation, observation, and reflection. The subjects of the study were 12 grade V students. Data were collected through learning outcome tests, observation, and documentation. The results showed that the use of the Canva-based PjBL model was able to improve students' writing learning outcomes. In cycle I, the average student learning outcomes reached 72.3 with a completion rate of 67%, while in cycle II, learning outcomes increased to 85.7 with a completion rate of 93%. Thus, the application of the Canva-based PjBL learning model is effective in improving students' writing skills in the Indonesian language subject.